X‐chromosome inactivation in female patients with Fabry disease. Issue 1 (22nd June 2015) - Echevarria, L.; Benistan, K.; Toussaint, A.; Dubourg, O.; Hagege, A.A.; Eladari, D.; Jabbour, F.; Beldjord, C.; De Mazancourt, P.; Germain, D.P.
Abstract : Fabry disease (FD) is an X‐linked genetic disorder caused by the deficient activity of lysosomal α‐galactosidase (α‐Gal). While males are usually severely affected, clinical presentation in female patients may be more variable ranging from asymptomatic to, occasionally, as severely affected as male patients. The aim of this study was to evaluate the existence of skewed X‐chromosome inactivation (XCI) in females with FD, its concordance between tissues, and its contribution to the phenotype. Fifty‐six females with FD were enrolled. Clinical and biological work‐up included two global scores [Mainz Severity Score Index (MSSI) and DS3], cardiac magnetic resonance imaging, measured glomerular filtration rate, and measurement of α‐Gal activity. XCI was analyzed in four tissues using DNA methylation studies. Skewed XCI was found in 29% of the study population. A correlation was found in XCI patterns between blood and the other analyzed tissues although some punctual variability was detected. Significant differences in residual α‐Gal levels, severity scores, progression of cardiomyopathy and deterioration of kidney function, depending on the direction and degree of skewing of XCI were evidenced. XCI significantly impacts the phenotype and natural history of FD in females.